Employing Respondent Driven Sampling (RDS) to recruit people who inject drugs (PWID) and other hard-to-reach populations during COVID-19: Lessons learned - Abadie, Roberto; Habecker, Patrick; Carrasco, Kimberly Gocchi; Chiou, Kathy S.; Fernando, Samodha; Bennett, Sydney J.; Valentin-Acevedo, Aníbal; Dombrowski, Kirk; West, John T.; Wood, Charles (Frontiers in Psychiatry, 2022)
Background: Respondent Driven Sampling (RDS) is an effective sampling strategy to recruit hard-to-reach populations but the impact of the Covid-19 epidemic on the use of this strategy in the collection of data involving human subjects, particularly among marginalized and vulnerable populations this disrupted is not known. Based on an ongoing study using RDS to recruit and study the interactions between HIV infection, injection drug use, and the microbiome in Puerto Rico, this paper explores the effectiveness of the employment of Respondent Driven Sampling during the pandemic and provided potential strategies that could improve recruitment and data collection. Results: RDS was employed to evaluate its effectiveness in recruiting a group of people with injection drug use (PWID) and controls (N=128) into a study in the midst of the COVID-19 pandemic. The participants were distributed along three subsets: 15 people were HIV+ & PWID, 59 were HIV- and PWID, and 54 were HIV+ and not PWID. Findings: Results show that recruitment through peer networks using RDS was possible across all sub-groups. Yet, while those in the HIV+ and PWID sub-group managed to recruit from other-sub groups of HIV-/PWID and HIV+, this occurred at a lower frequency. Conclusion: Despite the barriers introduced by Covid-19, it is clear that even in this environment, RDS continues to play a powerful role in recruiting hard-to-reach populations. Yet, more attention should be paid at how future pandemics, natural disasters, and other big events might affect RDS recruitment of vulnerable and hard-to-reach populations. Keywords: Respondent Driven Sampling; recruitment; PWID; HIV; Covid-19; Puerto Rico Employing Respondent Driven Sampling (RDS) to recruit hard-to-reach populations during Covid-19: Lessons Learned.